EXPERIMENTAL INVESTIGATION OF LAMINAR NATURAL CONVECTION HEAT TRANSFER IN A RECTANGULAR ENCLOSURE WITH AND WITHOUT INSIDE PARTITIONS (Journal of Engineering, 2011)
Experimental study has been conducted for laminar natural convection heat transfer of air flow through a rectangular enclosure fitted with vertical partition. The partition was oriented parallel to the two vertical isothermal walls with different temperatures, while all the other surfaces of the enclosure were insulated. In this study a test rig has been designed and constructed to allow studying the effect of Rayleigh number, aperture height ratio, partition thickness, the position of aperture according to the side walls and according to the height, the position of the partition according to the hot wall, and partition inclination. The experiments were carried out with air as the working fluid for Rayleigh number range (5*107 – 1.3*108) and aspect ratio of (0.5). 22 different configurations of partition were used in this study these are:a) Undivided enclosure (no – partition).b) (21) Cork partitions of different shapes.Empirical correlations for average Nusselt number are obtained for the different cases tested. The results show that heat transfer is independent on the partition position according to the cold wall and according to the upper or lower walls, while it shows that heat transfer is sensitive to:1. Rayleigh number (Ra), which increase with increasing Ra.2. Aperture height ratio (Ap=hp/H), which is found that when Ap= 5/6 (case 2,3), the reduction in heat transfer is 10.3%, while when Ap=1/2 (case 4,5), the reduction is 17.2% compared with the non partitioned enclosure.3. Aperture position according to the height, which is found that when the aperture at the centre of the partition (case 13), the reduction in heat transfer is 16.7%, while when the aperture displaced to the upper surface (case 14), the reduction is 19% compared with the non partitioned enclosure.4. Partition thickness (t), which is found that when t = 10 mm (case 4,5) the reduction in heat transfer is 17.2%, while when t = 150 mm (case 16) the reduction is 20.5% compared with the non partitioned enclosure.5. Partition inclination (), which is found that the rate of heat transfer reduced with increasingas shown:a. For = 30 toward the cold wall (case 22), the reduction in heat transfer is 18.2%.b. For = 45 toward the cold wall (case 18), the reduction in heat transfer was 21.9%.c. For = 60 toward the cold wall (case 20), the reduction in heat transfer is 30.2%.d. For = 30 toward the hot wall (case 21), the reduction in heat transfer is 31.3%.e. For = 45 toward the hot wall (case 17), the reduction in heat transfer is 40.7%.f. For = 60 toward the hot wall (case 19), the reduction in heat transfer is 42.1%.